Археологічні дослідження у Києві по вул. Десятинній, 11- А - Козловський, А.О.; Ієвлев, М.М.; Крижановський, В.О. (Археологічні дослідження в Україні, 2009)
The article elucidates the results of excavations at an interesting and little studied area of «the city of Volodymyr» at 11-A, Desyatynna Street. The data obtained allows the authors to state about habitation on this territory since the 11th c., testified by three objects of Ancient Rus time. Secondary settlement of this area started not earlier than the end of the 18th c. or the beginning of the 19th c.